2020
DOI: 10.1109/access.2019.2962202
|View full text |Cite
|
Sign up to set email alerts
|

Precious Metal Price Prediction Based on Deep Regularization Self-Attention Regression

Abstract: It is non-trivial to predict the prices of precious metals since a number of factors can affect the fluctuations of precious metal prices. Either parametric models or machine learning models cannot accurately forecast the precious metal prices. Though deep learning approaches show their strengths in extracting key features from complicated data, they have the limitations of learning localization and losing some temporal and spatial features. The recent advances in attention mechanisms bring the opportunities t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Then, attention map and matrix are multiplied to derive the attention feature matrix. The attention mechanism used is similar to the self-attention mechanism used in [ 32 ]. However, we have not used linear regulizers.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…Then, attention map and matrix are multiplied to derive the attention feature matrix. The attention mechanism used is similar to the self-attention mechanism used in [ 32 ]. However, we have not used linear regulizers.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…The authors in [11,31] found that the ARIMA model is more robust in short-term prediction. However, it cannot achieve convergence in the long term [33]. This means that the prediction accuracy of ARIMA will get worse in the long run.…”
Section: Related Workmentioning
confidence: 99%
“…This assumption makes it fail to capture the non-linear pattern from financial time-series data. Secondly, it does not converge to the financial time-series in the long-term causing more computational cost [33]. Lastly, it only accepts univariate time-series data, thus means it is challenging for ARIMA to imitate technical traders by using technical indicators and stock prices.…”
Section: Related Workmentioning
confidence: 99%
“…In summary, most researchers mainly use an algorithm model for customer churn early warning, but they have not used a variety of algorithm models for customer churn prediction and comparison (Buenano-Fernandez et al, 2020;Zhou et al, 2020). Some scholars specifically include control variable analysis for large-scale multiobjective optimization problems (Ma et al, 2021b), Some scholars summarize multidisciplinary writing styles and then predict author identification (Tai et al, 2020).…”
Section: Related Researchmentioning
confidence: 99%